Nitro Compounds and Their Derivatives in Organic Synthesis - Nishiwaki, Nagatoshi (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nitro chemistry plays an important role in organic synthesis to construct new frameworks. This is due to the diverse properties of the nitro group. The strong electron-withdrawing ability of the nitro group reduces the electron density of the scaffold, facilitating reactions with nucleophiles or electron transfer. In addition, the -hydrogen of the nitro group is highly acidic, giving a stable anion, which facilitates reactions with both electrophilic and nucleophilic reagents. In addition, the nitro group also serves as a good leaving group, which facilitates transformation to a wide variety of functional groups. Despite the substantial contributions of many researchers, nitro chemistry is still an exciting and challenging research area. This book brings together recent original research and review articles contributed by an international team of leading experts and pioneers in organic synthesis using nitro groups. It is sure to provide useful information and promising insights for researchers.